215 Demographic, clinical and paraclinical features in a subgroup of patients with NMOSD. Issue 12 (14th November 2019) - Wegehaupt, Thomas; Vundavalli, Sriram; Cooper, Sarah; Leite, Maria; Palace, Jacqueline; Fisniku, Leonora
Abstract : Background: Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune, inflammatory condition more commonly distinguished from multiple sclerosis (MS). Early diagnosis is paramount as NMOSD and MS respond to different immunomodulatory therapies. Objective: To determine common clinical and paraclinical features at the disease onset of NMOSD-patients. Methods: All antibody-positive NMOSD-patients seen between 2013 and 2017 at Brighton and Sussex University Hospital were included. Their clinical and paraclinical data at the first presentation was reviewed. Results: 9 patients were included; 8 caucasians; 5 females. Mean age at the onset was 48.8 years. All MOG-positive patients (5/9) presented with optic neuritis; AQP4-positive patients (4/9) presented with transverse myelitis or area postrema syndrome. One patient (AQP4-positive) had an underlying malignancy. Three patients had positive oligoclonal bands. None fulfilled the McDonald radiological criteria for MS. Brain MRI scan was abnormal in 5/9 patients with the lesions being either juxtacortical or subcortical but none periventricular. Spinal cord lesions were 2 or more vertebral length (range 2 – 10) and were isotense. No silent spinal cord lesions were seen. One patient required more than one immunosuppression (AQP4-positive) and one (MOG-positive) was on none. Conclusion: Early recognition of NMOSD-patients is important in order to direct appropriate treatment.